(untitled) (Journal of Comparative Social Work, 2025)
Ubuntu is an indigenous African philosophy that promotes collectivism, solidarity and mutual interdependence as being vital for the majority welfare. In this paper, it is used to discuss the findings from a qualitative study of how older people living with HIV (OPLHIV) in Korogwe, Tanzania use help groups for informal social support, to battle their daily challenges as a result of HIV and ageing in a rural context. Interviews with 13 OPLHIV showed that there are voluntarily formed groups and arranged groups. We find that voluntarily organised groups seem to build on, and benefit from Ubuntu values. The study further showed that Ubuntu values in group organisation are currently challenged by donor dependency, heterogeneity and poverty in local communities. Social work practice is recommended to acknowledge the strength of Ubuntu to support already existing initiatives in the field, but also to recognise the factors that challenge it.